DEFINING THE UNDEFINABLE: OPERATIONALIZATION OF METHODS TO IDENTIFY SPECIFIC LEARNING DISABILITIES AMONG PRACTICING SCHOOL PSYCHOLOGISTS. Issue 2 (17th December 2015) - Cottrell, Joseph M.; Barrett, Courtenay A.
Abstract : Accurate and consistent identification of students with specific learning disabilities (SLDs) is crucial; however, state and district guidelines regarding identification methods lack operationalization and are inconsistent throughout the United States. In the current study, the authors surveyed 471 school psychologists about school SLD identification guidelines and the identification methods actually used (e.g., ability‐achievement discrepancy, response‐to‐intervention, and the evaluation of students' pattern of strengths and weaknesses). Results indicated that nearly half the participants were allowed or required to choose the method of identification that ensured students received services, if the school‐based team determined services were warranted. Variations in SLD identification methods were also found between schools with different characteristics (e.g., location, school level, and student composition). Implications for practice are discussed.